2013
DOI: 10.5114/pjp.2013.36006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phototherapy in psoriasis on ki-67 antigen expression: a preliminary study

Abstract: Antigen Ki-67 is a non-histone nuclear protein, closely connected with cell proliferation. Determining Ki-67 allows for a quick and reliable evaluation of the growth fraction of the studied cell population. It serves as a marker of proliferative activity in neoplasms and other diseases with excessive cell proliferation such as psoriasis. Evaluation of Ki-67 expression in epidermal cells was performed in 10 individuals suffering from plaque psoriasis, before and after one of three methods of phototherapy: broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…PASI score is a universally accepted clinical indica-tor of disease severity in plaque type psoriasis. We studied plaque patients with PASI score ranging from 5.2 to 44.2 (mean 18.32) and found significantly higher Ki-67 expression in patients with PASI more than 10 as compared to those with PASI under 10, which is consistent with the findings of authors who have noted a positive correlation between clinical psoriatic activity (PASI) and epidermal proliferative activity (17,18). According to the European S3 Guidelines on the systemic treatment of psoriasis vulgaris, moderate to severe disease is defined as a PASI score >10 and is an indication for systemic treatment (19).…”
Section: Discussionsupporting
confidence: 89%
“…PASI score is a universally accepted clinical indica-tor of disease severity in plaque type psoriasis. We studied plaque patients with PASI score ranging from 5.2 to 44.2 (mean 18.32) and found significantly higher Ki-67 expression in patients with PASI more than 10 as compared to those with PASI under 10, which is consistent with the findings of authors who have noted a positive correlation between clinical psoriatic activity (PASI) and epidermal proliferative activity (17,18). According to the European S3 Guidelines on the systemic treatment of psoriasis vulgaris, moderate to severe disease is defined as a PASI score >10 and is an indication for systemic treatment (19).…”
Section: Discussionsupporting
confidence: 89%
“…Ki67 is a marker of cell proliferation and is therefore found in high levels in psoriatic lesions [ 108 ]. Some authors showed that Ki67 expression decreases after therapy [ 109 ].…”
Section: The Quest For Biomarkers In Psoriasismentioning
confidence: 99%
“…Another study showed that Ki-67 is a feasible marker of proliferation in the initial phase of adult neurogenesis [27]. Furthermore, previous studies have claimed that reduced Ki-67 expression was discovered after different kinds of treatment were applied to psoriatic skin lesions [28,29]. In this study, the results showed reduced Ki-67 expression after treatment with forsythoside A, implying that it inhibits epidermal proliferation in psoriatic skin lesions.…”
Section: Discussionmentioning
confidence: 54%